Structure of a human IgA1 Fab fragment at 1.55 Å resolution: potential effect of the constant domains on antigen‐affinity modulation. (24th March 2013) - Correa, Agustin; Trajtenberg, Felipe; Obal, Gonzalo; Pritsch, Otto; Dighiero, Guillermo; Oppezzo, Pablo; Buschiazzo, Alejandro
<x xml:space="preserve">Abstract</x> Despite being the most abundant class of immunoglobulins in humans and playing central roles in the adaptive immune response, high‐resolution structural data are still lacking for the antigen‐binding region of human isotype A antibodies (IgAs). The crystal structures of a human Fab fragment of IgA1 in three different crystal forms are now reported. The three‐dimensional organization is similar to those of other Fab classes, but FabA1 seems to be more rigid, being constrained by a hydrophobic core in the interface between the variable and constant domains of the heavy chain (VH–CH1) as well as by a disulfide bridge that connects the light and heavy chains, influencing the relative heavy/light‐chain orientation. The crystal structure of the same antibody but with a G‐isotype CH1 which is reported to display different antigen affinity has also been solved. The differential structural features reveal plausible mechanisms for constant/variable‐domain long‐distance effects whereby antibody class switching could alter antigen affinity.